Impacts of Whole-Genome Triplication on MIRNA Evolution in Brassica rapa - Sun, Chao (Genome Biol Evol, 2015)
MicroRNAs (miRNAs) are a class of short non-coding, endogenous RNAs that play essential roles in eukaryotes. Although the influence of whole-genome triplication (WGT) on protein-coding genes has been well documented in Brassica rapa, little is known about its impacts on MIRNAs. In this study, through generating a comprehensive annotation of 680 MIRNAs for B. rapa, we analyzed the evolutionary characteristics of these MIRNAs from different aspects in B. rapa. First, while MIRNAs and genes show similar patterns of biased distribution among subgenomes of B. rapa, we found that MIRNAs are much more overretained than genes following fractionation after WGT. Second, multiple-copy MIRNAs show significant sequence conservation than that of single-copy MIRNAs, which is opposite to that of genes. This indicates that increased purifying selection is acting upon these highly retained multiple-copy MIRNAs and their functional importance over singleton MIRNAs. Furthermore, we found the extensive divergence between pairs of miRNAs and their target genes following the WGT in B. rapa. In summary, our study provides a valuable resource for exploring MIRNA in B. rapa and highlights the impacts of WGT on the evolution of MIRNA.